Sustainable Corrosion Prevention: A Theoretical Synthesis of Renewable Materials and Bio-Inhibitors - Henry Chukwuemeka Olisakwe; Nwakamma Ninduwezuor-Ehiobu; Daniel Raphael Ejike Ewim (Journal of Research and Innovation for Sustainable Society)
Corrosion is a pervasive issue with significant environmental and economic impacts, necessitating the development of sustainable and effective prevention methods. This review synthesizes the literature on renewable materials and bio-inhibitors, both of which offer environmentally friendly alternatives to traditional chemical inhibitors. Renewable materials such as biopolymers and natural fibers provide durable, biodegradable barriers against corrosion, while bio-inhibitors, derived from plants and microbes, offer chemical protection by neutralizing corrosive agents. This paper proposes a new theoretical framework that integrates these two approaches, leveraging the strengths of renewable materials as carriers for bio-inhibitors to enhance corrosion resistance. The potential for synergistic effects between the two components is explored, highlighting their combined capability to offer long-term, eco-friendly corrosion protection across diverse industrial applications. Future research directions focus on improving these materials' scalability, durability, and customization for specific environmental conditions. By advancing the development of sustainable corrosion prevention systems, this integrated approach contributes to global efforts to reduce environmental pollution and improve material longevity.